Supercritical carbon dioxide extraction of pomegranate peel-seed mixture: yield and modelling - Tan, Wei Kiat; Lee, Sin Yee; Lee, Wan Jun; Hee, Yen Yi; Zainal Abedin, Nur Hanani; Abas, Faridah; Chong, Gun Hean (Elsevier, 2021)
By-products produced during the processing of pomegranate (Punica granatum L.) juice are currently undervalued and discarded, hence, this study investigated the effects of temperature (30–60 °C) and pressure (10–40 MPa) on the supercritical carbon dioxide (scCO2) extraction of a mixture of pomegranate peels and seeds (1:1) at a fixed CO2 flow rate of 10 L/min (0.1 MPa, 25 °C). The global yield increased with temperature but decreased with pressure, with the highest global yield (11.5%) obtained at 40 MPa and 40 °C. The reaction constants (0.044–0.066 min−1) and activation energy (6.06 kJ/mol) were determined with the first-order model. The Pardo-Castaño model I correlated with the experimental data with an average absolute relative deviation (AARD) of 6.1%, with the Chrastil model correlating with the solubility data with an AARD of 2.5%. The synergistic effect of PME was demonstrated with regard to yield as it had a higher extract to seed ratio.